(untitled) (Superficies y Vacío, 2013)
In this work we studied the influence of annealing atmosphere and Eu doping in the structural transformation on TiO2nanofibers, grown by electrospinning technique. The TiO2 samples were annealing to different temperatures under controlled atmosphere of Nitrogen and air. The TiO2:Eu samples were annealing in air atmosphere. The morphology has been studied by Scanning Electron Microscopy (SEM) and crystalline structure was analyzed by X-Ray Diffraction (DRX) and Raman. The nitrogen atmosphere promotes at lower temperatures the anatasa to rutilo transformation, compared with the air atmosphere. The Eu impurification increases the annealing temperature for the anatasa to rutile transformation.